2021
DOI: 10.12688/wellcomeopenres.17263.1
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and health in Southeast Asia – defining research priorities and the role of the Wellcome Trust Africa Asia Programmes

Abstract: This article summarises a recent virtual meeting organised by the Oxford University Clinical Research Unit in Vietnam on the topic of climate change and health, bringing local partners, faculty and external collaborators together from across the Wellcome and Oxford networks. Attendees included invited local and global climate scientists, clinicians, modelers, epidemiologists and community engagement practitioners, with a view to setting priorities, identifying synergies and fostering collaborations to help def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Despite the specific conditions of the English public health system, we identified several themes that have been mentioned in previous literature. Substantial concern about the impacts of climate change on health were almost ubiquitous in studies16 19–22 in line with international agencies’ concerns 23–25. Evidence suggests however that action to protect health is inadequate, a recent review of local authority climate change plans found that 80% of all local authorities have a climate change plan, but only 50% included reference to the health impacts of the climate crisis 26.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the specific conditions of the English public health system, we identified several themes that have been mentioned in previous literature. Substantial concern about the impacts of climate change on health were almost ubiquitous in studies16 19–22 in line with international agencies’ concerns 23–25. Evidence suggests however that action to protect health is inadequate, a recent review of local authority climate change plans found that 80% of all local authorities have a climate change plan, but only 50% included reference to the health impacts of the climate crisis 26.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore possible that the use of data of much greater granularity from meteorological, hydrological, entomological, and behavioural sources could translate into models with better performance. Novel methods of data acquisition utilising mHealth or drone technologies could provide the necessary substrates for more precise modelling ( 8 ). Clinical prediction models have traditionally focused only on patient variables, but machine learning approaches are inherently scalable systems and can integrate large datasets from diverse sources.…”
Section: Discussionmentioning
confidence: 99%
“…Low-cost and robust molecular diagnostics are much needed and developments are underway (7), but their widespread implementation currently remains infeasible. With the backdrop of human-induced climate change, new autochthonous transmission and changing seasonal epidemiology of dengue, new tools to support clinical diagnosis, and management are warranted (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%